2014
DOI: 10.1007/s11604-014-0300-6
|View full text |Cite
|
Sign up to set email alerts
|

First experience of carbon-ion radiotherapy for early breast cancer

Abstract: Breast cancer is increasingly being detected at earlier stages, and partial breast irradiation for patients with low-risk-group tumor has come to be applied in the US and Europe as an alternative to whole-breast irradiation. Based on those experiences, some institutes have tried using particle beams for partial breast irradiation for postoperative or radical intent for early breast cancer, but technical difficulties have hindered its progress. The National Institute of Radiological Sciences has been preparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…Accordingly, these ion beams bring about more cell cycle-and oxygenation-independent, irreparable DNA damage and eradicate more resistant cancer cells than conventional radiation [149,150]. Recently, a phase I clinical trial of early stage breast cancer treated with heavy ion irradiation noticed a limitations of dose escalation owing to adverse effects of skin, ribs, and lungs after carbon ion radiotherapy, particularly for some aggressive subtypes of breast cancer such as TNBC [30,151]. The authors considered that carbon ion beam combined with chemotherapy might decrease the dose of irradiation but preserve certain advantages to eliminate breast cancer [30,151].…”
Section: Carbon Ion Beam Combined With Cisplatin Effectively Disruptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, these ion beams bring about more cell cycle-and oxygenation-independent, irreparable DNA damage and eradicate more resistant cancer cells than conventional radiation [149,150]. Recently, a phase I clinical trial of early stage breast cancer treated with heavy ion irradiation noticed a limitations of dose escalation owing to adverse effects of skin, ribs, and lungs after carbon ion radiotherapy, particularly for some aggressive subtypes of breast cancer such as TNBC [30,151]. The authors considered that carbon ion beam combined with chemotherapy might decrease the dose of irradiation but preserve certain advantages to eliminate breast cancer [30,151].…”
Section: Carbon Ion Beam Combined With Cisplatin Effectively Disruptsmentioning
confidence: 99%
“…Recently, a phase I clinical trial of early stage breast cancer treated with heavy ion irradiation noticed a limitations of dose escalation owing to adverse effects of skin, ribs, and lungs after carbon ion radiotherapy, particularly for some aggressive subtypes of breast cancer such as TNBC [30,151]. The authors considered that carbon ion beam combined with chemotherapy might decrease the dose of irradiation but preserve certain advantages to eliminate breast cancer [30,151]. The combination of chemotherapy with heavy ion radiotherapy might open new means to counteract this challenging breast cancer subgroup which has poor prognosis and highly limited treatment choices.…”
Section: Carbon Ion Beam Combined With Cisplatin Effectively Disruptsmentioning
confidence: 99%
“…However, this assessment 3 months after C-ion RT was then considered premature, based on the results of "Advanced Medicine" patients, and the Phase I study (UMIN ID000010848) of 7 patients was discontinued. Akamatsu et al had reported the treatment procedure and initial course of the rst case 10 , and the subsequent course is shown in Figure 1. In this patient, it took 24 months for tumor disappearance on MRI, but uorodeoxyglucose (FDG) positron emission tomography (PET) showed a signi cant reduction in accumulation at 2 months and complete disappeared at 9 months.…”
Section: Discussionmentioning
confidence: 99%
“…For position recognition, two ducial markers were inserted 5 mm from the upper and lower border of the intraductal extension. The details of preparation, positioning, and treatment planning were previously reported 10 . Gross tumor volume (GTV) was de ned as the volume of tumor based on contrast MRI ndings.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…Tumors which are not good candidates for conventional radiotherapy: more than 1000 bone and soft tissue sarcomas, nearly 1000 melanomas, sarcomas, adenocarcinomas and related pathologies of head and neck tumors, more than 800 lung cancers, more than 500 liver tumors, nearly 500 pancreatic cancers, nearly 500 pelvic recurrences of rectal cancer, and more than 250 uterine cancers have been treated at NIRS [9]. Until 2011, a systemic approach for breast cancer by C-ion RT had not been carried out, as breast cancer has relatively good prognosis with other multivariate treatment modalities [10]. We started preparing for C-Ion RT for breast cancer in 2011, and started a The most important selection criterion of C-ion RT for recurrent tumors is the so-called oligometastasis, or whether the patient has other metastases that are well controlled by systemic treatment.…”
Section: Discussionmentioning
confidence: 99%